Difference between revisions of "Euler's identity"

m
m (Minor edit)
 
Line 9: Line 9:
 
<math>(\cos(\theta) + i\sin(\theta))^n = (e^{i\theta})^n = e^{in\theta} = \cos(n\theta) + i\sin(n\theta)</math>.
 
<math>(\cos(\theta) + i\sin(\theta))^n = (e^{i\theta})^n = e^{in\theta} = \cos(n\theta) + i\sin(n\theta)</math>.
  
===Sine/Cosine Angle Addition Formulas===
+
=== Sine/Cosine Angle Addition Formulas ===
  
 
Start with <math>e^{i(\alpha + \beta)} = (e^{i\alpha})(e^{i\beta})</math>, and apply Euler's forumla both sides:
 
Start with <math>e^{i(\alpha + \beta)} = (e^{i\alpha})(e^{i\beta})</math>, and apply Euler's forumla both sides:
 
+
<cmath>\cos(\alpha + \beta) + i \sin(\alpha + \beta) = (\cos\alpha + i\sin\alpha)(\cos\beta + i\sin\beta).</cmath>
<math>
 
\cos(\alpha + \beta) + i \sin(\alpha + \beta) = (\cos\alpha + i\sin\alpha)(\cos\beta + i\sin\beta).</math>
 
 
 
 
Expanding the right side gives
 
Expanding the right side gives
 
+
<cmath>(\cos\alpha\cos\beta - \sin\alpha\sin\beta) + i(\cos\alpha\sin\beta + \sin\alpha\cos\beta).</cmath>
<math>
 
(\cos\alpha\cos\beta - \sin\alpha\sin\beta) + i(\cos\alpha\sin\beta + \sin\alpha\cos\beta).
 
</math>
 
 
 
 
Comparing the real and imaginary terms of these expressions gives the sine and cosine angle-addition formulas:
 
Comparing the real and imaginary terms of these expressions gives the sine and cosine angle-addition formulas:
 
+
<cmath>\cos(\alpha+\beta) = \cos\alpha\cos\beta - \sin\alpha\sin\beta</cmath>
<math>
+
<cmath>\sin(\alpha+\beta) = \cos\alpha\sin\beta + \sin\alpha\cos\beta</cmath>
\cos(\alpha+\beta) = \cos\alpha\cos\beta - \sin\alpha\sin\beta
 
</math>
 
 
 
<math>
 
\sin(\alpha+\beta) = \cos\alpha\sin\beta + \sin\alpha\cos\beta
 
</math>
 
  
 
===Geometry on the complex plane===
 
===Geometry on the complex plane===
Line 36: Line 23:
 
===Other nice properties===
 
===Other nice properties===
  
A special, and quite fascinating, consequence of Euler's formula is the identity <math>e^{i\pi}+1=0</math>, which relates five of the most fundamental numbers in all of mathematics: [[e]], [[imaginary unit | i]], [[pi]], [[zero (constant)| 0]], and 1.
+
A special, and quite fascinating, consequence of Euler's formula is the identity <math>e^{i\pi}+1=0</math>, which relates five of the most fundamental numbers in all of mathematics: [[e]], [[imaginary unit|i]], [[pi]], [[0]], and [[1]].
  
 
==Proof 1==
 
==Proof 1==
Line 43: Line 30:
  
 
We have the following Taylor series:
 
We have the following Taylor series:
 
+
<cmath>e^x=1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\cdots=\sum_{k=0}^{\infty}\frac{x^k}{k!}</cmath>
<math>e^x=1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\cdots=\sum_{k=0}^{\infty}\frac{x^k}{k!}</math>
+
<cmath>\sin(x)=x-\frac{x^3}{3!}+\frac{x^5}{5!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k+1}}{(2k+1)!}</cmath>
 
+
<cmath>\cos(x)=1-\frac{x^2}{2!}+\frac{x^4}{4!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k}}{(2k)!}</cmath>
<math>\sin(x)=x-\frac{x^3}{3!}+\frac{x^5}{5!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k+1}}{(2k+1)!}</math>
 
 
 
<math>\cos(x)=1-\frac{x^2}{2!}+\frac{x^4}{4!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k}}{(2k)!}</math>
 
  
 
The key step now is to let <math>x=i\theta</math> and plug it into the series for <math>e^x</math>.  The result is Euler's formula above.  
 
The key step now is to let <math>x=i\theta</math> and plug it into the series for <math>e^x</math>.  The result is Euler's formula above.  
Line 54: Line 38:
 
==Proof 2==
 
==Proof 2==
 
Define <math>z=\cos{\theta}+i\sin{\theta}</math>. Then <math>\frac{dz}{d\theta}=-\sin{\theta}+i\cos{\theta}=iz</math>, <math>\implies \frac{dz}{z}=id\theta</math>
 
Define <math>z=\cos{\theta}+i\sin{\theta}</math>. Then <math>\frac{dz}{d\theta}=-\sin{\theta}+i\cos{\theta}=iz</math>, <math>\implies \frac{dz}{z}=id\theta</math>
 +
<cmath>\int \frac{dz}{z}=\int id\theta</cmath>
 +
<cmath>\ln{|z|}=i\theta+c</cmath>
 +
<cmath>z=e^{i\theta+c}<math>; we know </math>z(0)=1<math>, so we get </math>c=0<math>, therefore </math>z=e^{i\theta}=\cos{\theta}+i\sin{\theta}</cmath>.
  
<math>\int \frac{dz}{z}=\int id\theta</math>
+
== See Also ==
 
 
<math>\ln{|z|}=i\theta+c</math>
 
  
<math>z=e^{i\theta+c}</math>; we know <math>z(0)=1</math>, so we get <math>c=0</math>, therefore <math>z=e^{i\theta}=\cos{\theta}+i\sin{\theta}</math>.
 
 
== See Also ==
 
 
*[[Complex numbers]]
 
*[[Complex numbers]]
 
*[[Trigonometry]]
 
*[[Trigonometry]]
Line 68: Line 50:
  
 
[[Category:Complex numbers]]
 
[[Category:Complex numbers]]
 +
{{stub}}

Latest revision as of 10:19, 15 February 2025

Euler's Formula is $e^{i\theta}=\cos \theta+ i\sin\theta$. It is named after the 18th-century mathematician Leonhard Euler.

Background

Euler's formula is a fundamental tool used when solving problems involving complex numbers and/or trigonometry. Euler's formula replaces "cis", and is a superior notation, as it encapsulates several nice properties:

De Moivre's Theorem

De Moivre's Theorem states that for any real number $\theta$ and integer $n$, $(\cos(\theta) + i\sin(\theta))^n = (e^{i\theta})^n = e^{in\theta} = \cos(n\theta) + i\sin(n\theta)$.

Sine/Cosine Angle Addition Formulas

Start with $e^{i(\alpha + \beta)} = (e^{i\alpha})(e^{i\beta})$, and apply Euler's forumla both sides: \[\cos(\alpha + \beta) + i \sin(\alpha + \beta) = (\cos\alpha + i\sin\alpha)(\cos\beta + i\sin\beta).\] Expanding the right side gives \[(\cos\alpha\cos\beta - \sin\alpha\sin\beta) + i(\cos\alpha\sin\beta + \sin\alpha\cos\beta).\] Comparing the real and imaginary terms of these expressions gives the sine and cosine angle-addition formulas: \[\cos(\alpha+\beta) = \cos\alpha\cos\beta - \sin\alpha\sin\beta\] \[\sin(\alpha+\beta) = \cos\alpha\sin\beta + \sin\alpha\cos\beta\]

Geometry on the complex plane

Other nice properties

A special, and quite fascinating, consequence of Euler's formula is the identity $e^{i\pi}+1=0$, which relates five of the most fundamental numbers in all of mathematics: e, i, pi, 0, and 1.

Proof 1

The proof of Euler's formula can be shown using the technique from calculus known as Taylor series.

We have the following Taylor series: \[e^x=1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\cdots=\sum_{k=0}^{\infty}\frac{x^k}{k!}\] \[\sin(x)=x-\frac{x^3}{3!}+\frac{x^5}{5!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k+1}}{(2k+1)!}\] \[\cos(x)=1-\frac{x^2}{2!}+\frac{x^4}{4!}-\cdots=\sum_{k=0}^{\infty}(-1)^{k}\frac{x^{2k}}{(2k)!}\]

The key step now is to let $x=i\theta$ and plug it into the series for $e^x$. The result is Euler's formula above.

Proof 2

Define $z=\cos{\theta}+i\sin{\theta}$. Then $\frac{dz}{d\theta}=-\sin{\theta}+i\cos{\theta}=iz$, $\implies \frac{dz}{z}=id\theta$ \[\int \frac{dz}{z}=\int id\theta\] \[\ln{|z|}=i\theta+c\] \[z=e^{i\theta+c}<math>; we know </math>z(0)=1<math>, so we get </math>c=0<math>, therefore </math>z=e^{i\theta}=\cos{\theta}+i\sin{\theta}\].

See Also

This article is a stub. Help us out by expanding it.